2021
DOI: 10.3390/en14061759
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Heat Recovery in Ventilation

Abstract: The purpose of the article was to present information on heat recovery in ventilation systems and to highlight what has not been sufficiently researched in this regard. A lot of information can be found on methods and exchangers for heat recovery in centralized systems. Decentralized, façade systems for cyclical supply and exhaust air have not been sufficiently researched. It is known that these devices are sensitive to the influence of wind and temperature, hence heat recovery may be ineffective in their case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 143 publications
0
15
0
2
Order By: Relevance
“…The use of mechanical ventilation, especially for outdoor air pollution, is essential [30]. Other previously mentioned advantages include the possibility of air filtering and the use of heat recovery [47]. The use of small, dedicated, one-room ventilation units does not have to be expensive [48].…”
Section: Possibilities To Improve Indoor Air Qualitymentioning
confidence: 99%
“…The use of mechanical ventilation, especially for outdoor air pollution, is essential [30]. Other previously mentioned advantages include the possibility of air filtering and the use of heat recovery [47]. The use of small, dedicated, one-room ventilation units does not have to be expensive [48].…”
Section: Possibilities To Improve Indoor Air Qualitymentioning
confidence: 99%
“…This is accomplished by centrifugal fan with 6-level adjustable air speeds varied from 10 m 3 /h to 60 m 3 /h. One being installed at the supply air side and another at the exhaust air outlet (Zender-świercz, 2021;Mardiana-Idayu and Riffat, 2012;Cuce and Riffat, 2015). An example of integrating the window heat recovery system in the building is presented in Fig.…”
Section: Window Heat Recovery Systemmentioning
confidence: 99%
“…Energy consumption in buildings is responsible for around 40% of the total energy demand in the EU (Ekins and Lees, 2008). Building heating, cooling and ventilation represents between 40%-60% of the total consumption (Zender-świercz, 2021), where ventilation itself is between 20%-30% (National Institute for Health and Welfare, 2013). Several studies indicated that building ventilation will significantly affect occupants' health (Cao and Ren, 2018;Yuan et al, 2018), indoor air quality (Lim et al, 2021;González Couret et al, 2013), heating/cooling demand (Tien et al, 2021;Zuazua-Ros et al, 2019) and energy consumption (Young et al, 2020;Bang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This has been supported by several studies, for example, by the results of experimental studies of hot water consumption Energies 2021, 14, 8217 2 of 28 in single-family houses [2], by the analysis of hybrid hot water preparation systems for an industrial hall [3] and by the analysis of the possibility of using renewable energy sources for heating hot water [4]. In the case of ventilation systems, reduction in energy demand can be achieved by using heat recovery systems from the exhaust air [5]. Especially favorable are decentralized systems, in which the low flow resistance of the installation combined with better adaptation to the current needs of users result in significant energy and primary energy savings for residential buildings [6][7][8] but also for swimming pools [9] or for kindergartens [10].…”
Section: Introductionmentioning
confidence: 99%